Association of edaphoclimatic characteristics and variability of condensed tannin content in species from Caatinga (Revista Ciência Agronômica, 2020)
Condensed tannin (CT) concentrations in plants are influenced by species, plant part, season, growth phase,environmental conditions, disease and defoliation. The objectives of this study were to determine the effects of edaphoclimaticfactors on the concentration of CT stored in leaves and bark from Mimosa tenuiflora (Wild.) Poiret and Anadenantheramacrocarpa (Benth.) Brenan., collected at three distinct locations in northeastern Brazil. At each study site, sampling wascarried out by randomly selecting five trees, each tree represented one replication and samples of leaves and bark of eachplant species was collected. Soil samples were collected near the base of each plant for moisture, physical and chemicalanalysis. Meteorological data from each month and site were obtained of the INMET automatic station. We conducted aprincipal components analysis using a multivariate technique to observe the influence of soil and weather on condensed tanninconcentration. Overall, Anadenanthera macrocarpa has the least total CT concentration in both plant fraction and site. Ourresults suggest that soil chemical characteristics, soil moisture and weather explain 76.27% and 75.92% of the variation in CTproduced by Mimosa tenuiflora and Anadenanthera macrocarpa, respectively. Condensed tannin concentration in these twospecies is negatively associated with soil moisture and rainfall, and positively associated with temperature and soil chemicalelements.